Infrared-to-visible upconversion in Yb3+/Er3+ co-doped PbO-GeO2 glass with silver nanoparticles - Bomfim, F. A.; Martinelli, J. R.; Kassab, L. R P [UNESP]; Assumpcao, T. A. A.; de Araujo, C. B. (Elsevier B.V., 2010)
Enhanced frequency upconversion (UC) emission was studied in Yb3+/Er3+ co-doped PbO-GeO2 glass containing silver nanoparticles (NPs). Optical excitation was achieved with a laser operating at 980 nm in resonance with the Yb3+ transition F-4(5/2)-> F-4(7/2). The intensity of the whole UC spectrum from 400 to 700 nm was intensified due to the influence of silver NPs. The green and red emissions were enhanced by more than 300%. Emission bands centered at 408 nm and 480 nm were also detected corresponding to the H-2(9/2)-> I-4(15/2) and F-4(7/2)-> I-4(15/2) transitions of Er3+ ion. An intensity enhancement of approximate to 150% due to the NPs was measured. For the first time the influence of silver NPs on the blue emission of Yb3+/Er3+ co-doped PbO-GeO2 glass is reported. The large enhancement in the whole UC spectrum is due to the increased local field in the Er3+ ions locations and the proximity between the luminescence wavelengths and the NPs surface plasmon resonance. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Silver nanoparticles; Upconversion; Rare earths; Energy transfer